Primary pigmented nodular adrenocortical disease - Marie T Manipadam; Rachel Abraham; Sudipta Sen; Anna Simon (Wolters Kluwer Medknow Publications, 2011)
Primary pigmented nodular adrenocortical disease (PPNAD) is a rare cause of ACTH-independent Cushing's syndrome and has characteristic gross and microscopic pathologic findings. We report a case of PPNAD in a 15-year-old boy, which was not associated with Carney's complex. Bilateral adrenalectomy is the treatment of choice.